CRTH2 mediates the activation of human Th2 cells in response to PGD(2) released from IgE/anti-IgE treated nasal polyp tissue. - Pérez-Novo, C; Holtappels, G; Vinall, S; Xue, L; Zhang, N; Bachert, C; Pettipher, R (2010)
BACKGROUND: Mast cells release mediators upon stimulation that contribute to the pathogenesis of chronic airway disease, including the recruitment and activation of Th2 lymphocytes. The objective was to determine the involvement of prostaglandin D(2) (PGD(2)) and its receptors in the chemotaxis of Th2 cells, using nasal polyp tissue. METHODS: Tissue explants from ten patients with nasal polyposis were incubated with RPMI alone or RPMI containing IgE/anti-IgE for 30 min. Some samples were treated with diclofenac to inhibit the production of PGD(2). Supernatants were assayed for PGD(2) content and for their ability to promote human Th2 cell chemotaxis in the presence and absence of a CRTH2 antagonist. Transcript levels of D protanoid receptor type 1 (DP(1)), chemoattractant receptor-homologous receptor expressed on Th2 cells (CRTH2) and PGD(2) synthase were analysed by real time PCR. RESULTS: Increased release of PGD(2) by nasal polyp tissue treated with IgE/anti-IgE was significantly inhibited by preincubation of the tissue with diclofenac. Transcript levels of PGD(2) synthase, DP(1) and CRTH2 receptors increased after stimulation with IgE/anti-IgE. Supernatants from IgE/anti-IgE-stimulated nasal polyp tissue caused significantly increased chemotaxis of Th2 cells. The levels of PGD(2) produced and the degree of Th2 cell chemotaxis were highly correlated. Diclofenac inhibited the production of Th2 cell chemotactic activity, and the chemotactic effect of the supernatant on Th2 cells was inhibited by the CRTH2 antagonist ramatroban. CONCLUSION: These data suggest that in immunologically activated nasal polyp tissue, PGD(2) produced by mast cells promotes the migration of Th2 cells through a CRTH2 dependent mechanism.